The flexible structure of the K24S28 region of Leucine-Rich Amelogenin Protein (LRAP) bound to apatites as a function of surface type, calcium, mutation, and ionic strength - Lu, Jun-xia; Burton, Sarah D.; Xu, Yimin S.; Buchko, Garry W.; Shaw, Wendy J. (Frontiers in Physiology, 2014)
Leucine-Rich Amelogenin Protein (LRAP) is a member of the amelogenin family of biomineralization proteins, proteins which play a critical role in enamel formation. Recent studies have revealed the structure and orientation of the N- and C-terminus of LRAP bound to hydroxyapatite (HAP), a surface used as an analog of enamel. The structure of one region, K24 to S28, was found to be sensitive to phosphorylation of S16, the only naturally observed site of serine phosphorylation in LRAP, suggesting that K24S28 may sit at a key region of structural flexibility and play a role in the protein’s function. In this work, we investigated the sensitivity of the structure and orientation of this region when bound to HAP as a function of several factors which may vary during enamel formation to influence structure: the ionic strength (0.05 M, 0.15 M, 0.2 M), the calcium concentration (0.07 mM and 0.4 mM), and the surface to which it is binding (HAP and carbonated apatite (CAP), a more direct mimic of enamel). A naturally occurring mutation found in amelogenin (T21I) was also investigated. The structure in the K24S28 region of the protein was found to be sensitive to these conditions, with the CAP surface and excess Ca2+ (8:1 [Ca2+]:[LRAP-K24S28(+P)]) resulting in a tighter helix, while low ionic strength relaxed the helical structure. Higher ionic strength and the point mutation did not result in any structural change in this region. The distance of the backbone of K24 from the surface was most sensitive to excess Ca2+ and in the T21I-mutation. Collectively, these data suggest that phosphorylated LRAP is able to accommodate structural changes while maintaining its interaction with the surface, and provides further evidence of the structural sensitivity of the K24S28 region, a sensitivity that may contribute to function in biomineralization.